2018
DOI: 10.1002/ijgo.12486
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BRCA mutations on outcomes among patients with serous endometrial cancer

Abstract: Although not significant, BRCA mutation carriers tended to have more advanced disease at diagnosis. However, the survival was similar irrespective of the BRCA status in this small group. Further research is needed to confirm these findings in a larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(65 reference statements)
2
12
1
1
Order By: Relevance
“…Patients with BRCA1 and BRCA2 mutations had more favorable outcomes than noncarriers in endometrial carcinoma, which differ from the results of previous studies. There were no signi cant differences identi ed in prognosis of uterine serous carcinoma between BRCA mutation carriers and noncarriers [17]. In addition, our ndings differ from the analysis of ovarian cancer data from the Cancer Genome Atlas project, and another study that found that patients with BRCA2 mutation had more favorable prognosis than BRCA2 non-carriers [19,23].…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…Patients with BRCA1 and BRCA2 mutations had more favorable outcomes than noncarriers in endometrial carcinoma, which differ from the results of previous studies. There were no signi cant differences identi ed in prognosis of uterine serous carcinoma between BRCA mutation carriers and noncarriers [17]. In addition, our ndings differ from the analysis of ovarian cancer data from the Cancer Genome Atlas project, and another study that found that patients with BRCA2 mutation had more favorable prognosis than BRCA2 non-carriers [19,23].…”
Section: Discussioncontrasting
confidence: 98%
“…To the best of our knowledge, this study was the rst to investigate the effect of BRCA mutations on the prognosis of endometrioid endometrial carcinoma. Patients with BRCA1 mutations presented with higher risk disease than non-carrier group and BRCA2 mutation carriers [17]. Among endometrioid endometrial carcinoma group, there were more patients with BRCA1 or BRCA2 mutation than non-carrier group in our study.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations